Computational fluid dynamic (CFD) simulation of synthetic jet cooling: a review - Ariffin, Ahmad Hamdan; Ahmad, Kamarul Ariffin (Penerbit Akademia Baru, 2020)
Synthetic jet which is also known as pulsed jet is a mechanism that is applied in many industries, such as manufacturing, automotive, and electronics. It is used in the industries as a cooling device. There have been many products developed and experimental data gained in the previous decade from synthetic jet technology. Interestingly, the expansion in computational fluid dynamic (CFD) simulation for synthetic jet analysis becomes important due to the technical advantages in reducing the analysis time and cost of the test rig. Therefore, this paper reviews the parameters in the CFD simulation which affects the synthetic jet performance. The parameters involved are synthetic configuration, numerical method modelling, and cavity. The numerical methods employed are Shear Stress Transport, Reynolds Averaged Navier- Stokes (RANS), k-ε, and Lattice Boltzmann. The investigation on synthetic jet via CFD analysis still needs further enhancement, especially on numerical method selection and modification. In certain conditions, the results of CFD simulation perform very close to the real experimental data. Therefore, the CFD technology is crucial to expedite the synthetic jet product enhancement.